The treatment of war wounds in Graeco-Roman antiquity - Salazar, Christine F. (Studies in Ancient Medicine, 2000)
In this investigation of the treatment of battle trauma in antiquity, 'treatment' is used in a double sense, both as actual medical treatment and literary 'treatment' in non-medical sources. Part I deals with the practical, medical aspects of the topic: the types of wounds likely to result from a battle, their surgical and pharmacological treatment, the question of medical services in ancient armies, medical terminology and the availability of medical knowledge. Part II discusses the use of scenes of wounding and wound treatment in literature, and Part III is a survey of the archaeological evidence. This is the first monograph to examine the topic in all its different aspects; it should be of interest to classicists, medical historians and military historians.